Do public transfers crowd out private transfers? Evidence from a randomized experiment in Mexico - Pedro Albarran; Orazio P. Attanasio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The paper will use the data from the PROGRESA evaluation to show the extent to which such a programme crowds out private transfers. An interesting aspect of the paper is the fact that it can use the randomization (one-third of the villages in the sample were randomized in the programme for evaluation purposes).
Keywords: O16; I30; 330; private transfers; crowding-out; public programmes; Ländliche Armut; Armutspolitik; Privater Transfer; Öffentlicher Transfer; Crowding out; Mexiko